Exclusive Stopping Space for Motorcycles (ESSM) technical design at signalized intersections - Muh Akbar; Dewi Sriastuti Nababan; Daud Andang Pasalli (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The growth of motorcycles which continues to increase every year can lead to an increase in the number of accumulation of motorcycles on the approach to the intersection, so it is necessary to plan a Exclusive Stoping Spaces for Motorcycle (ESSM). The purpose of this study is to find out whether the street at the research location meets the requirements for ESSM planning by reviewing the number of motorbikes piled up during the red phase and planning the ESSM design. The method used in this study is an experimental method in accordance with the 2014 Indonesian Highway Capacity Guidelines (PKJI) and the Technical Planning Guidelines for Special Stopping Spaces in urban areas. The results of the study show that ESSM at signalized intersections in urban areas in Merauke City can be implemented in the next 15 years, namely in 2037. Of the four arms of signalized intersections, only 3 approaches can implement ESSM facilities, namely the Brawijaya Street approach, the TMP Street approach, and Parakomando Street approach. While the Angkasa Street approach cannot be applied to ESSM because it does not meet the requirements in the ESSM planning guidelines. The ESSM design on the Brawijaya Street approach uses a 2-lane box type ESSM with an area of 60 m2; on the TMP Street approach using a 2-lane box type ESSM with an area of 60 m2; on the Parakomando Street approach using a 2-lane box type ESSM with an area of 56 m2.